Overkill? An Examination of Comparatively Excessive Death Sentences in North Carolina, 1990–2010. (23rd February 2017) - Cochran, John K.; Brown, Wyatt; Camacho, Jocelyn; Jennings, Wesley G.; Smith, M. Dwayne; Bjerregaard, Beth; Fogel, Sondra J.
Abstract : This study examines death/life capital sentences in one southern state, North Carolina, during the period 1990 to 2010 to determine the extent to which they are comparatively excessive/lenient. The study employs data derived from a variety of official sources on the population of capital trials in the state during this timeframe and follows the analytic techniques developed by David Baldus and his colleagues and by Paternoster and Kazyaka in their studies of comparative excessiveness in capital sentencing in California, Georgia, and South Carolina, respectively. The results show a substantial number of death sentences that meet the standard for excessiveness, but the data also show a nearly equal number of life sentences that may be deemed too lenient. The implications of these findings are discussed.